The role of top-down and bottom-up factors in parafoveal reading - Bandiera, Valentina; Primativo, Silvia; Daini, Roberta; Martelli, Marialuisa; Arduino, Lisa S. (Frontiers in Cognition, 2025)
Recently we have shown that, while reading two words presented simultaneously, one in the fovea and one in the parafovea, participants are more accurate and faster when the two words are semantically related. The present study confirmed and supported the previous results by using the same Rapid Parallel Visual Presentation Paradigm (RPVP) and by changing the relative proportions of unrelated vs. semantically related word pairs. Indeed, differently from other studies where semantically unrelated and related word pairs were equally represented (50% each), in the present study only 30% of word pairs were semantically related. Results showed again an advantage when the two words were semantically related and we interpreted these findings in terms of automaticity between lexical/sublexical units processing and semantic access.